CandiDating Game: An Exercise in Interviewing and Hiring. (March 2022) - Howe, David C.
This article describes a game show-style classroom exercise that is appropriate for any management-related courses that wish to enrich students' understanding of a key phase of the hiring process. The activity introduces the importance of job descriptions and job specifications through a semiscripted unstructured interview patterned after a classic television game show. In The CandiDating Game, one student interviews three candidates in front of the class. Through varying the job specifications that each student receives without informing the students or interviewer, the instructor can use this activity to engage the class in a rigorous discussion on the importance of job specifications and the general structure of interviews.